2022
DOI: 10.1021/acs.jpclett.2c01822
|View full text |Cite
|
Sign up to set email alerts
|

Water-Controlled Structural Transition and Charge Transfer of Interfacial Ionic Liquids

Abstract: Clarification of the water-induced structural transitions and electron transfer between ionic liquids (ILs) and a solid surface allows for establishing a unified view of the electrical properties of interfacial ILs via a hitherto unexplored pathway. Here, we propose a simple and effective method to quantitatively identify and extract the transferred electrons between ILs and a solid surface, while demonstrating the critical structural transition of interfacial ILs from ordered stripe structures to disordered a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Therefore, we analyzed the effect of the Lorentz force on the magnetic field and introduced the viscosity as an intermediate value to study the change in the liquid surface tension caused by the high magnetic Lorentz force. It is well known that the liquid surface tension γ LG is related to the viscosity η 40 • kT m 15 16 LG (4) where k is the Boltzmann constant (1.380649 × 10 −23 m 2 kg s −2 k −1 ), T is the absolute temperature, and m is the atomic mass. Based on Stokes's law and the additional viscosity resistance caused by a high magnetic field, Sun et al 41,42 deduced the relationship between the viscosity of liquid with and without a high magnetic field…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we analyzed the effect of the Lorentz force on the magnetic field and introduced the viscosity as an intermediate value to study the change in the liquid surface tension caused by the high magnetic Lorentz force. It is well known that the liquid surface tension γ LG is related to the viscosity η 40 • kT m 15 16 LG (4) where k is the Boltzmann constant (1.380649 × 10 −23 m 2 kg s −2 k −1 ), T is the absolute temperature, and m is the atomic mass. Based on Stokes's law and the additional viscosity resistance caused by a high magnetic field, Sun et al 41,42 deduced the relationship between the viscosity of liquid with and without a high magnetic field…”
Section: Resultsmentioning
confidence: 99%
“…Ionic liquids have emerged as versatile functional materials in many research fields, and they have diverse applications from energy conversion to material manufacturing. A critical property that governs their performance is the surface wettability, which determines the contact and adhesion between the ionic solution and the surface and describes the solid–liquid–gas three-phase system. For example, suitable wettability of the catalyst ensures effective charge transfer and electrocatalytic efficiency in the electrocatalytic process. , Good wettability of the separator in the battery to the ionic electrolyte reduces the battery internal resistance, improving the battery performance and service life. , Additionally, ionic liquids show promise as probe fluids for surface energy characterization owing to their unique wetting properties . A comprehensive understanding of the ionic liquid wettability on surfaces is thus very important.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They can self-assemble into a variety of specific structures in solvents, and many of them eventually form lamellar crystals at low enough temperatures. Although there have been extensive studies on the crystallization phase transitions of amphiphilic molecules, including phospholipids, , surfactants, and amphiphilic ionic liquids, except for the studies on the air–water surface and solid substrates, no report on the dispersion of amphiphile-based 2DCs in liquid medium is seen, to the best of our knowledge. This brings about the following academic question: How important is the layer–layer interaction to the crystallization of amphiphiles?…”
mentioning
confidence: 99%
“…Their findings suggested that the charging time for supercapacitors lengthens as the anion size increases, which is due to larger anions obstructing the ion movement. The investigation of water structure and transport of humid ILs in nanopores is critical, given the hygroscopic nature of ILs. Shi et al explored the ionic transport of humid ILs in the subnanopores through both experimental measurements and MD simulations. Their results indicated that the ion transport and charging dynamics of subnanometer pores with functional groups can be enhanced by stabilizing confined water.…”
mentioning
confidence: 99%